ANALISIS STRATEGI PEMASARAN PRODUK WAKAF PADA PT. SUN LIFE FINANCIAL SYARIAH CABANG KOTA TANGERANG - Fifin Afrilina; Nihayatul Masykuroh (Syar'Insurance: Jurnal Asuransi Syariah, 2019)
Sun Life Financial Syariah Tangerang City Branch is a financial services company that provides a variety of products including waqf products for insurance benefits. The fundamental challenge in optimizing waqf programs in Indonesia is that understanding of the waqf law is good and right by some people, some people do not know about waqf money / cash, lack of socialization about endowments of insurance benefits. this requires PT. Sun Life Financial Syariah needs a special strategy to attract public interest in waqf products The formulation of the problems that can be raised in this study are (1) how the waqf product marketing strategy carried out by PT. Sun Life Financial Syariah Tangerang City Branch, (2) how the SWOT analysis that affects marketing strategies based on internal and external factors at PT. Sun Life Financial Syariah in marketing waqf products. The purpose of this study are (1) To find out the application of waqf product marketing strategies at PT. Sun Life Financial Syariah Tangerang City Branch, (2) to find out the results of the SWOT analysis that affects the marketing strategy based on internal and external factors. The method used in this study is a qualitative method which is a research procedure that produces data from direct interviews in the form of written or oral words from the parties concerned then analyzed using SWOT analysis. From the results of the research, the waqf product marketing strategy undertaken by PT. Sun Life Financial Syariah Tangerang City Branch namely marketing strategies through agents, and marketing strategies through collaboration with institutions. The result of the SWOT analysis is the strategy adopted by the company is the strategy of concentration through vertical integration (cell 1), growth through concentration can be achieved through vertical integration by means of backward integration (taking over the supplier function) or by means of forward integration (taking over the distributor function). This is the main strategy for companies that have strong competition in high-attraction industries.